The role of financial analysis in evaluating the financial performance of commercial banks: An applied study in the Erbil Bank for Investment and Finance in Sulaymaniyah Governorate - Muhealddin, Banaz Ahmad; Salih, Nyaz Osman (Journal of University of Human Development, 2024)
This research aims to explain the role of financial analysis in evaluate financial performance in commercial banks in general and its application to the Erbil investment and finance bank in particular, Explaining the importance of the information provided by financial analysis to management .Financial analysis is considered an important tool that contributes to sound financial planning processes in commercial banks .The financial manager in banks must review the financial position before thinking about setting policies related to planning operations and future expectations .The data used in the research were obtained from the published annual reports and financial statements of the Erbil bank for investment and finance in Sulaymaniyah Governorate regarding its activity for the period from the year 2018 t0 the end of the year 2020,as well as the websites of the bank in question .The results of the research show that the trading ratio of assets and liabilities was good during the years (2018,2020),his ratio gives a high degree of safety to deposit holders and investors ,However this percentage decreased during the year 2019, and the bank must change its policies by increasing its assets to address this situation .The ratio of debts to total assets during the three years was low, and this is an indicator that indicates a reeducation in debts ,burdens ,and financial risks to which shareholders and creditors are exposed ,and provides them with stability and security .Also the interest coverage ratio to gross profit was high during (2018), This indicates the banks ability to cover its obligations .This percentage decreased during the years (2019,2020) and the reason for this is due to the bank achieving a loss during the years mentioned previously The most important thing that the two researchers recommend is the need to pay attention to the financial analyses process ,because of its importance in accessing the data contained in the financial statements .and identifying the financial position of banks .Through it, financial performance is improved, and the banks ability to increase its assets compared to its liabilities in order to achieve the highest turnover rate to enable it to fulfill its obligations. In addition to the need for the bank to invest its money in various fields and invest its money by granting advances and loans.